Cognitive curiosity of kindergarten child (building &applying) (Journal of the College of Basic Education, 2026)
The current research aims to identify :1-The cognitive curiosity of kindergarten child.2- The differences in relation of cognitive curiosity of kindergarten child according to the gender (male – female) . To achieve the two aims of research the researchers have chosen the research community from kindergarten children in city of Baghdad with its both sides Karkh & Rusafa .the research sample was (150) children . the test of cognitive curiosity has built which includes (14) items , & psychometric characteristics like (validity & reliability) has achieved .After using statistical methods (T- test of one sample , T-test of two samples ) it reached to the following results ;The kindergarten children have cognitive curiosity .There are no differences in cognitive curiosity between kindergarten children according to the gender ( male – female ) .